The Etiology of the Traumatic Abdominal Injuries in Diyarbakır, Turkey: A 4-Year Retrospective Analysis - Yiğit, Ebral; Taş, İlhan (Cerrahpaşa Medical Journal, 2021)
Objective: The injury mechanism of abdominal trauma differs worldwide and within individual countries. The aim of this study was to determine the most common etiology of abdominal trauma in our region and evaluate the factors that affect the mortality and morbidity of the patients. Methods: This retrospective study was conducted in the general surgery department of Gazi Yaşargil Training and Research Hospital from January 2016 to December 2020. All patients admitted with a diagnosis of abdominal trauma during the study period were included in the study, regardless of age or gender. A total of 240 patients with abdominal trauma were examined. Depending on the type of injury, conservative or operative treatment was used. Postoperatively, the patients were followed up for detection and treatment of complications. Results: Penetrating trauma was more common than blunt trauma. Of the patients, 212 (88.3%) were male and 28 (11.7%) were female. Most patients were within the age group of 21 to 30 years. The liver was the most frequently injured solid organ, while the small intestine was the most commonly injured hollow viscus organ. Traffic accidents were the most common causes of blunt trauma, and knife injuries were the most common cause of penetrating abdominal trauma. The mortality rate was higher among the patients with gunshot wounds than among those with other trauma etiologies. Conclusion: The study results show that the liver was the most frequently injured solid organ, and the small intestine was the most commonly injured hollow viscus organ. Firearm injury is the most common cause of death. Cite this article as: Yiğit E, Taş İ. The etiology of the traumatic abdominal injuries in Diyarbakır, Turkey: A 4-year retrospective analysis. Cerrahpaşa Med J. 2021;45(3):135-140.